Safety and efficacy of Soyo-san for the treatment of functional dyspepsia: A protocol for systematic review and meta-analysis - Ha, Na-Yeon (Medicine (Baltimore), 2020)
BACKGROUND: Functional dyspepsia (FD) is a common condition characterized by gastrointestinal symptoms, such as abdominal fullness and epigastric pain. With the limitations of conventional Western medical treatments, symptoms often recur and lead to poor quality of life. Soyo-san (SYS) is a traditional herbal medicine that has been frequently used to treat indigestion. This protocol was designed to investigate the safety and efficacy of SYS for treating FD through a systematic review and meta-analysis. METHODS: Trials will be searched from the following 11 electronic databases, up to March 2020: EMBASE, Medline (via PubMED), the Cochrane Central Register of Controlled Trials (CENTRAL), Allied and Complementary Medicine Database (AMED), Korean Medical Database (KMbase), KoreaMed, Korean Studies Information Service System (KISS), National Digital Science Library (NDSL), Oriental Medicine Advanced Searching Integrated System (OASIS), China National Knowledge Infrastructure Database (CNKI), and Citation Information by Nii (CiNii). Randomized controlled trials (RCTs) of SYS or modified SYS for FD will be included in this systematic review. The effects of control interventions such as placebo, no-treatment, and conventional Western medicine will be compared with those of SYS. RCTs investigating the synergetic effect of SYS and Western medicine compared with conventional Western medicine alone will also be evaluated. Two investigators will independently extract the data and assess the risk of bias in the included studies. The total clinical effective rate will be measured as the main outcome. RESULTS: This systematic review will provide data on the use of SYS in the treatment of FD, based on indicators such as dyspepsia-related symptom score, recurrence rate, and adverse events. CONCLUSION: This study will determine the safety and efficacy of SYS for the treatment of FD. REVIEW REGISTRY UNIQUE IDENTIFYING NUMBER: reviewregistry969.